Melting of PP/PA6 polymer blends in single screw extruders: an experimental study - Cunha, S. M. (2008)
A prototype modular single screw extruder fitted with a screw extracting device is used to monitor melting of an immiscible polymer blend (PP/PA6, with different weight ratios) in this widely used processing equipment. As anticipated, the phenomena observed are much more complex than those involved in extruding PP or PA6, when the well known Maddock/Tadmor mechanism is valid. Consequently a hybrid melting mechanism, involving Maddock/Tadmor and Dispersive melting sequences, is proposed.